2020
DOI: 10.1515/multi-2018-0130
|View full text |Cite
|
Sign up to set email alerts
|

‘With the greatest sincerity’: expressing genuineness of feeling in nineteenth-century business correspondence in English

Abstract: This article is concerned with the history of yours sincerely, a popular closing formula in English epistolary discourse. The formula was already used sporadically in the seventeenth century, gradually increased in frequency in the Late Modern period, and was the preferred subscription in English business correspondence by the end of the 1950s. This study investigates patterns of usage of closing formulae in a bestselling business letter-writing manual William Anderson’s Practical Mercantile Correspondence, A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Studies of leavetaking formulae in the late modern period have approached these from different angles, either focusing on the use of the extended your humble servant formula, on its variation with other, potentially shorter, forms or on the rise of the short formulae yours sincerely and yours affectionately. Research on late 18th-and 19th-century business correspondence has found that these letters rely to a large degree on the deferential servant formula, which is interpreted as an indicator of the social distance between the correspondents (Del Lungo Camiciotti 2006: 160-161;Dollinger 2008: 268;Morton 2016: 193-199;Shvanyukova 2020). Overall, the servant formula seemed relatively fixed regarding its modification patterns.…”
Section: Epistolary Leavetaking Formulaementioning
confidence: 99%
See 1 more Smart Citation
“…Studies of leavetaking formulae in the late modern period have approached these from different angles, either focusing on the use of the extended your humble servant formula, on its variation with other, potentially shorter, forms or on the rise of the short formulae yours sincerely and yours affectionately. Research on late 18th-and 19th-century business correspondence has found that these letters rely to a large degree on the deferential servant formula, which is interpreted as an indicator of the social distance between the correspondents (Del Lungo Camiciotti 2006: 160-161;Dollinger 2008: 268;Morton 2016: 193-199;Shvanyukova 2020). Overall, the servant formula seemed relatively fixed regarding its modification patterns.…”
Section: Epistolary Leavetaking Formulaementioning
confidence: 99%
“…While in formal and asymmetrical contexts, the extended servant formula continued to be an appropriate letter subscription well into the 19th century (Del Lungo Camiciotti 2006: 161;Morton 2016: 199;Shvanyukova 2020, see also Section 4.2.1), it is especially in the letters exchanged between correspondents of equal social status that a routinisation of this formula can be observed. On the one hand, we can see a conventionalisation of the semantically bleached servant slot leading to its structural reduction.…”
Section: Simplification As Indicator Of Ongoing Functional Changementioning
confidence: 99%